Landslides Hazard Assessment Using Different Approaches - Coman Cristina (Mathematical Modelling in Civil Engineering, 2017)
Romania represents one of Europe’s countries with high landslides occurrence frequency. Landslide hazard maps are designed by considering the interaction of several factors which, by their joint action may affect the equilibrium state of the natural slopes. The aim of this paper is landslides hazard assessment using the methodology provided by the Romanian national legislation and a very largely used statistical method. The final results of these two analyses are quantitative or semi-quantitative landslides hazard maps, created in geographic information system environment. The data base used for this purpose includes: geological and hydrogeological data, digital terrain model, hydrological data, land use, seismic action, anthropic action and an inventory of active landslides. The GIS landslides hazard models were built for the geographical area of the Iasi city, located in the north-east side of Romania.